The emperor's new groove ; Kronk's new groove [videorecording (DVD)] - Bour, Elliot M.; Blinkoff, Saul Andrew; Spade, David; Goodman, John, 1952-; Kitt, Eartha (Disney Blu-ray., 2013)
After Emperor Kuzco is turned into a llama by his devious advisor, he turns to shepherd Pacha to help him regain his former life as ruler; Kronk, now the head chef in his own diner, becomes frantic when he learns his father is coming to visit and many misadventures happen as he prepares to impress his father.